Początki parafii Matki Bożej Królowej Korony Polskiej na Kijowskim Przedmieściu w Brześciu nad Bugiem - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2014)
Grassroots initiatives of the faithful of the city of Brześć, supported by the clergy, have been approved by the Ordinary of the Diocese of Pińsk - Bishop Zygmunt Łoziński, who on 16 October 1938 erected the parish in the Kiev Suburb in Brześć. For a growing number of the inhabitants of Brześć in the interwar period of the Second Polish Republic, the above- mentioned parish was established to meet the religious needs of the local Catholics. In August 1937, Rev. Wacław Piątkowski was mandated, by the Bishop of Pińsk, to create a parish with an indication of the Kiev Suburb, where he soon began celebrating daily liturgy in a temporary chapel. Organized in November 1937, the Church Social Construction Committee undertook the care of raising funds for the implementation of a costly venture. A temporary chapel was consecrated on 14 August 1938 by Rev. Wacław Piątkowski, a parish priest. On 30 July 1939 the Bishop of Pińsk consecrated the foundation stone of the church, and next day the construction of the foundations began. Until the outbreak of World War II, a concrete footing under the foundation of the church was made along with the necessary excavations. War and occupation: the Soviet and German prevented the implementation of the initiated project. During those years, priests performed pastoral service, not only in their own parishes but often helped other parishes which were deprived of priests because of the arrests of clergy and their deportation to concentration camps, as well as due to the moving of many priests to the west of the created in 1945 Polish-Soviet frontier on the Bug. Thanks to the clergymen who, despite everything, stayed after the war in the Diocese of Pińsk within the borders of Byelorussian SSR, the continuity of the hierarchical authority of the Church was preserved. That authority was exercised by the vicars general until the church administration had been organized within the borders of the Republic of Belarus.